INSTITUTIONAL SUPPORT FOR ATTRACTING AND REALIZING INVESTMENTS IN THE ENERGY SECTOR OF UKRAINE - Zatonatska, Tetiana; Zhylinska, Oksana; Ivanytskyi, Maksym (Socio-economic relations in the digital society, 2024)
The article analyzes the issues of adequateness of the institutional support for attracting and realizing investments in the energy sector of Ukraine to the current realities in which the country finds itself. The article emphasizes that public-private partnership is the basis for further attraction and realization of investments in the energy sector. The article highlights several issues such as attracting investment in the energy sector of Ukraine, and public-private partnership in the energy sector and identifies the ways to overcome them. The necessity of improving the legal framework in the field of public-private partnership; development of institutional infrastructure supporting public-private partnership; providing guarantees for protecting the interests of all parties in the public-private partnership throughout the entire life cycle of the project is substantiated. It is concluded that attracting and injecting investments in the energy sector is possible only in close cooperation with large private businesses by implementing elements and mechanisms of public-private partnership in the sector. It’s the only way that the energy sector of Ukraine will be able to adapt to modern challenges to ensure its long-term sustainable development.